Modeling Present and Future Permafrost Distribution at the Seward Peninsula, Alaska. Issue 8 (1st August 2020) - Debolskiy, M. V.; Nicolsky, D. J.; Hock, R.; Romanovsky, V. E.
Abstract: Permafrost, a key component of Arctic ecosystems, is currently affected by climate warming and anticipated to undergo further significant changes in this century. The most pronounced changes are expected to occur in the transition zone between the discontinuous and continuous types of permafrost. We apply a transient temperature dynamic model to investigate the spatiotemporal evolution of permafrost conditions on the Seward Peninsula, Alaska—a region currently characterized by continuous permafrost in its northern part and discontinuous permafrost in the south. We calibrate model parameters using a variational data assimilation technique exploiting historical ground temperature measurements collected across the study area. The model is then evaluated with a separate control set of the ground temperature data. Calibrated model parameters are distributed across the domain according to ecosystem types. The forcing applied to our model consists of historic monthly temperature and precipitation data and climate projections based on the Representative Concentration Pathway (RCP) 4.5 and 8.5 scenarios. Simulated near‐surface permafrost extent for the 2000–2010 decade agrees well with existing permafrost maps and previous Alaska‐wide modeling studies. Future projections suggest a significant increase (3.0°C under RCP 4.5 and 4.4°C under RCP 8.5 at the 2 m depth) in mean decadal ground temperature on average for the peninsula for the 2090–2100 decade when compared to the period of 2000–2010. Widespread degradation of the near‐surface permafrost is projected to reduce its extent at the end of the 21st century to only 43% of the peninsula's area under RCP 4.5 and 8% under RCP 8.5. Key Points: The ecosystem‐type approach is applied to simulate permafrost dynamics on the Seward Peninsula Improved regional scale model is used to simulate snow interception and scouring Enhanced model calibration approach is implemented to allow for better use of historical borehole data